2018
DOI: 10.1007/s11673-018-9865-6
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Issues of Using CRISPR Technologies for Research on Military Enhancement

Abstract: This paper presents an overview of the key ethical questions of performing gene editing research on military service members. The recent technological advance in gene editing capabilities provided by CRISPR/Cas9 and their path towards first-in-human trials has reinvigorated the debate on human enhancement for non-medical purposes. Human performance optimization has long been a priority of military research in order to close the gap between the advancement of warfare and the limitations of human actors. In spit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 37 publications
0
10
0
2
Order By: Relevance
“…This is not surprising given the heated ethical and social debate regarding germline gene editing and embryos. 1618 Indeed, recent studies on the public perception of gene editing show less public support for germline gene editing, especially for human enhancement. 19 It should also be emphasized that numerous articles could be characterized as being overly optimistic, indicating the presence of inappropriate science hype.…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising given the heated ethical and social debate regarding germline gene editing and embryos. 1618 Indeed, recent studies on the public perception of gene editing show less public support for germline gene editing, especially for human enhancement. 19 It should also be emphasized that numerous articles could be characterized as being overly optimistic, indicating the presence of inappropriate science hype.…”
Section: Discussionmentioning
confidence: 99%
“…These studies are commonly focused on increasing the tolerance of soldiers against biological or chemical warfare. This technology has the potential to influence human performance optimization (Greene and Master, 2018). Studies are usually concentrated on discovering different genes that can be harnessed from other species (Gracheva et al, 2010) and identifying new genes that can be associated with posttraumatic stress disorder, which is frequently experienced by soldiers (Cornelis et al, 2010).…”
Section: Military Applicationsmentioning
confidence: 99%
“…Another interesting study showed that the CMG2 gene, known to cause low sensitivity to anthrax toxin when expressed in small amounts, could be silenced by this technology (Arévalo et al, 2014). However, it should be noted that far more research needs to be conducted for using CRISPR technology in humans as a defense tool against biological and chemical weapons (Greene and Master, 2018).…”
Section: Military Applicationsmentioning
confidence: 99%
“…But it is more a case of horses for courses. There are a group of papers that address classical medical ethical issues such as professional responsibility and the duty to refer in cases of conscientious objection (Greenblum and Kasperbauer 2018), decision-making processes for dealing with possible return of genomic findings (Eckstein and Otlowski 2018), moral schism as a model for understanding parental experiences in neonatal ICU (Foe, Hellmann, and Greenberg 2018), debates about research participation, the therapeutic misconception, and human enhancement in the context of CRISPR technologies for military enhancement (Greene and Master 2018), and decisionmaking regarding apnoea testing for brain death (Lewis and Greer 2018).…”
mentioning
confidence: 99%
“…Common to a number of articles across both of these sets is discussion of the ethical complexities that arise when common dualisms begin to blur and bleed. This includes blurring of the personal and professional in the context of conscientious objection and the duty to refer (Greenblum and Kasperbauer 2018), between health and the market in relation to commodification of objects such as blood, gametes, and organs (Koplin 2018), between the research and clinical domains in the return of genomic findings (Eckstein and Otlowski 2018), and between health and enhancement when using CRISPR technologies in a military setting (Greene and Master 2018). Each of these articles reminds us of the need for critical reflection on taken-for-granted binaries that often underpin our ethical reasoning and it is here that an Bopening up to scrutiny^from those outside the specialized niche can provide great insight.…”
mentioning
confidence: 99%